Ewolucja działań rewitalizacyjnych w Polsce. Przegląd problematyki = Evolution of revitalisation activities in Poland. Review of the issues - Leszkowicz-Baczyński, Jerzy (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Revitalization activities have become an important component of contemporary urban policy. The author assumes that their beginning was marked by transformational changes at the turn of the 1980s and 1990s, resulting in an increase in the powers of municipal authorities. However, the very beginnings of revitalization were far from the correct understanding of the essence of this process, and the tasks performed consisted mainly in technical and renovation tasks.
Keywords: rewitalizacja społeczna; rewitalizacja miasta; ustawa rewitalizacyjna; blokady rewitalizacji; social revitalization; urban regeneration; revitalization act; obstacles to revitalization